A case study on effective elements that affect employees performance towards Matrix Concepts Holdings Bhd / Ahmad Fareez Mohd Yaacob and Nur Khairunnisa Mohamad Nek Ezar - Mohd Yaacob, Ahmad Fareez; Mohamad Nek Ezar, Nur Khairunnisa (Faculty of Business and Management, 2014)
This is a research to find out the effectiveness elements that can affect employee’s performance in MATRIX CONCEPTS HOLDING BERHAD. The objective of the study is to investigate the relationship between independent variables and dependent variable. The effective elements such as employees wellness program, stress and satisfaction and employee engagement determinants are the independents variables and employee performance as the dependent variables. About 100 employees from different departments will be the respondent and their answers are important finding. This study is a descriptive studies which to collect data that can describe the situation. The theoretical framework function is to show the relationship employees wellness program, stress and satisfaction and employee engagement determinants between with employee’s performance. The researchers will gather information from primary data which is by questionnaire (personally administered) and refer to the variety of secondary data which senior’s thesis, journal, article and Google. The sampling frame is among employees in MATRIX CONCEPTS HOLDING BERHAD and the sample size would be focused on 100 employees under Matrix Concepts in Seremban’s branch only in Sendayan, Negeri Sembilan. We used quota sampling since the number of respondent (employees) is fixed. To measure and scaling, interval scale is suits to this study as we want to recognize the employees preference throughout the list of questions in questionnaire. Statistical Package for the Social Science (SPSS) is an application that usually used by new researchers to analyze the data collected from questionnaires which will be gathered from the respondents. Questionnaire will be designed by researchers themselves which comprises with questions related to the dependent and independent variables. The data however showed that only one independent variable do have positive relationship and significance to the dependent variable which is employee wellness program.